Angkara: Short Film Exploration Of Bali Traditional Art Comedian Clekontong Emas - I Komang Arba Wirawan; Paul Trinidad; Nyoman Lia Susanthi (Journal of Art, Film, Television, Animation, Games and Technology, 2022)
The purpose of this study is to analyze the film titled Angkara. This film was produced by Dream House Production (DHP). DHP is a start-up for Film and Television Study Program students, a result of the academic learning process at the Indonesian Arts Institute Denpasar. In the DHP production team, the director of this film is Herda Martin Dwi Angga, and the producer is Robi'atul Yamania. DHP is a creative visual and production team that was formed in 2006. This film explores the traditional art of Balinese comedian (Bondres) Clekontong Mas, based on the social phenomena of Balinese society. This research is qualitative and descriptive, using a video recording of Angkara film. Then several scenes related to Mise En Scene were analyzed. The analysis of research and creation data was conducted by using the Mise En Scene creation theory. Baudrillard Mise En Scene was used to find out the setting, directing style, blocking, costumes, and lighting in the frame of this film. The results show that Angkara film used a traditional Balinese setting in 2018 with comedian directing style, in terms of blocking, the placement of Clekontong Emas as a supporting role was successful in comedy acting. The costumes of Angkara actors, with traditional Balinese characteristics, can describe the comedian's situation based on local Balinese wisdom. The social phenomenon that was told in this film managed to make this film win national and international festivals. Thus, Balinese traditional comedy can be a source of creating short films that have distinctive characteristics and are able to win film festivals.